El claroscuro de la sordidez en Las cruces sobre el agua - Robalino, Vicente (2024)
This essay highlights the fictionalization of the awakening of Guayaquil’s popular classes in the first decades of the twentieth century, through two axes: the realization of the situation of misery in which they live and the participation in two historical movements (the Concha Revolution and the strike of November 15, 1922). In this way, the characters of Las cruces sobre el agua cross a dark clearing where poverty, illness and death underlie. The protagonist, Alfredo Baldeón, finds himself trapped between the dilemma of starving to death or dying in the war. However, from this sordid space arises, in each of the characters, the hope of improving their life situation, through their participation in the strike of November 15, a hope cut short by repression and death. From this epic of horror remain, in the collective memory, the crosses that float on the water.